Chitosan: Properties and its pharmaceutical and biomedical aspects - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
Chitosan, a natural based nontoxic cationic polysaccharide polymer obtained by alkaline deacetylation of chitin, presents excellent properties such as biodegradability, antibacterial and wound-healing activity and immunological properties. These properties make chitosan a good candidate for the development of conventional and novel drug delivery systems. Chitosan has been used as a polymer for a controlled delivery system, gene delivery, scaffold, haemostatic action in wound healing, cell culture and cosmetic applications. Chitosan has become the focus of major interest in recent years because it has applications in not only the drug industry but also the agriculture, textile and paper industries. On the other hand, use of this biopolymer as a pharmaceutical excipient by different dose and for a number of applications is not new, but it still appears to be present in marketed drugs. The development of new delivery systems for controlled release of drugs is one of the most interesting areas of research in the pharmaceutical sciences. Nano and microparticles can be used for controlled release of different biological substances and drugs such as plasmids, hormones, peptide and proteins, antibiotics and vaccines. In this field, chitosan particular systems and chitosan matrixes, prepared by using different methods, can be used for encapsulating the drugs. Moreover, there has been interest in the chemical modification and PEGylated chitosan in order to improve its solubility and applications. Representatives of these novel chitosan modified polymers are carboxymethyl chitosan, thiolated chitosan, succinate and phthalate of chitosan salts and trimethyl-chitosan. The main chemical modifications of chitosan that have been proposed in the literature are reviewed in this chapter. Furthermore, recent studies suggested that chitosan and its derivatives are promising candidates as a supporting material for tissue engineering applications owing to their porous structure, gel forming properties, ease of chemical modification, high affinity to in vivo macromolecules. In general, this review provides an overview of using chitosan in pharmaceutical and biomedical applications. © 2011 by Nova Science Publishers, Inc. All rights reserved.